Trace elements in surface sediments from Kongsfjorden, Svalbard: occurrence, sources and bioavailability - Grotti, Marco; Soggia, Francesco; Ardini, Francisco; Bazzano, Andrea; MORONI, Beatrice; VIVANI, Riccardo; CAPPELLETTI, David Michele; Misic, Cristina (International Journal of Environmental Analytical Chemistry, 2017)
Concentration levels, potential sources and bioavailability of trace elements in marine sediments from Kongsfjorden (Svalbard Islands, Norwegian Arctic) were assessed and discussed. Surface sediments were collected by a Ponar grab and characterised in terms of mineralogical composition, grain-size distribution, total organic carbon and nitrogen percentage contents, and major and trace elements concentrations. Anthropogenic and natural sources of trace elements were inferred from lead isotope ratios, while the potential metal bioavailability was evaluated by size-fractionation and solid-phase speciation studies and by the analysis of acidvolatile sulphides (AVS) and simultaneously extracted metals (SEM). Concentrations of metals, their enrichment factors and solid speciation patterns collectively indicated that the anthropogenic impact of trace elements in the fjord is generally low, with a minor enrichment with respect to crustal values (by a factor of 2–11) for As, Cr, Ni and V. The lead isotope ratios (208Pb/207Pb: 2.474–2.498 and 206Pb/207Pb: 1.206–1.212) were close to the natural signature except in the outer fjord, due to the influence of the Atlantic marine circulation. Many elements of toxicological concern (e.g. Pb, V, Zn) were enriched in the finest sediment fraction, which was by far the preponderant one, especially in the inner fjord. However, less than 15% of most trace elements (exceptions Cd and Mn) in the finest fraction was actually associated with easily leachable sediment phases. Finally, the high SEM/AVS ratios determined on samples from sites close to the glacier fronts (11– 15), due to low AVS content, highlighted that the sediment in that zone cannot remove additional inputs of heavy metals by sulphide precipitation.